Raising awareness of environmental risks: A case study - Pinto, Lígia (2003)
We present a study of the effects of an abandoned mining site on the environmental and human health and discuss possible mechanism to raise public awareness of the risks posed by mining sites, and environmental risks in general. The case study reported concerns the Campo de Jales mining site located in the interior north of Portugal which is currently being sealed. The presentation and discussion are oriented by the actions lines established by the 6th environmental action programme.